Factors influencing housing purchase decision - Hassan, Mohammad Mujaheed; Ahmad, Nobaya; Hashim, Ahmad Hariza (Human Resource Management Academic Research Society, 2021)
House is among the essentials for human beings, which also functions as a protection and sustenance for household living. Although awning a “dream home” is the most desired life goal of individuals, it takes various aspects into account. Furthermore, provided that housing market results are based on diverse factors, this article attempts to identify and analyse the elements impacting a buyer’s housing purchase decision. However, the remaining unpurchased residential units in the nation are the results of inconsistent pricing, less appealing and other several factors. Generally, the government and private developers must identify primary elements influencing house purchase, prevent abandoned projects, guarantee the successful operation of projects, and fulfil the homeowners’ needs for the long term. Notably, this article is beneficial as a reference for future projects by researchers, developers, the government, and other professionals related to the housing industry.